A Case of New-Onset Dermatomyositis in the Second Trimester of Pregnancy: A Case Report and Review of the Literature - Tayfun Akalin; Hatice Akkaya; Barış Büke; İbrahim Koçak (Case Reports in Obstetrics and Gynecology)
Dermatomyositis (DM), a subtype of idiopathic inflammatory myopathies (IIMs), is characterized by skin rash, proximal muscle weakness, and inflammatory infiltrates in the muscle tissue. The peak incidence of the disease is at the age of 50–60 years, and only 14% of the patients with IIMs are estimated to present during reproductive years. Because of the limited pregnancy experience in patients with IIMs, little is known regarding the effects of DM on pregnancy or vice versa. We herein report a 40-year-old woman who developed DM in the second trimester of her pregnancy and did not respond to treatment with methylprednisolone. Her pregnancy was terminated at the 32nd week of gestation, due to preeclampsia and fetal distress. She delivered a healthy baby and improved rapidly after delivery. We have searched PubMed for relevant articles and reviewed previously published cases.